2024
DOI: 10.3390/applbiosci3010002
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Artificial Intelligence into Clinical Practice

Vangelis D. Karalis

Abstract: The purpose of this literature review is to provide a fundamental synopsis of current research pertaining to artificial intelligence (AI) within the domain of clinical practice. Artificial intelligence has revolutionized the field of medicine and healthcare by providing innovative solutions to complex problems. One of the most important benefits of AI in clinical practice is its ability to investigate extensive volumes of data with efficiency and precision. This has led to the development of various applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 189 publications
0
13
0
Order By: Relevance
“…Besides the extensive utilization of AI in diagnostic approaches, AI has also been integrated into various medical fields, including pneumonology, neurology, cardiology, gynecology, anesthesiology, surgery, urology, etc. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Data augmentation, utilized in various fields such as computer vision to assist AI models in better performing their tasks, has gained recognition in clinical trials [7,40].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the extensive utilization of AI in diagnostic approaches, AI has also been integrated into various medical fields, including pneumonology, neurology, cardiology, gynecology, anesthesiology, surgery, urology, etc. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Data augmentation, utilized in various fields such as computer vision to assist AI models in better performing their tasks, has gained recognition in clinical trials [7,40].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AI has the potential to predict treatments most likely to yield positive outcomes for individual patients, enabling personalized medicine tailored to unique patient characteristics. By optimizing administrative processes and reducing redundant tests, AI also holds promise for reducing healthcare expenses, both in terms of finances and time [11].…”
Section: Discussionmentioning
confidence: 99%
“…The number of AI applications has been increasing exponentially in recent years. In healthcare, there are numerous use cases of AI and machine learning, including drug discovery, medicine, dentistry, anesthesiology, and ophthalmology [11][12][13][14][15][16]. One recent application of AI proposed by our research group is data augmentation, which involves virtually increasing a sample by generating new data from existing data [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ethical considerations also include obtaining consent for using clinical data in generating synthetic datasets and addressing potential biases to ensure fairness and representativeness. Adhering to these steps will ensure that the synthetic data generated by generative AI algorithms are scientifically valid and ethically sound for clinical research [21].…”
Section: Discussionmentioning
confidence: 99%
“…The number of AI applications has been increasing exponentially in recent years. In healthcare, there are numerous use cases of AI and machine learning, including drug discovery, medicine, dentistry, anesthesiology, and ophthalmology [16][17][18][19][20][21]. Data augmentation has not been widely used in the healthcare industry; however a recent study from our lab has shown the efficiency and advantages of this approach in the field of clinical trials [22].…”
Section: Introductionmentioning
confidence: 99%